Risques d'inégalités liés à certaines caractéristiques des manuels contemporains de langues modernes en Belgique francophone - Germain Simons; Daniel Delbrassine; Florence Van Hoof (Nantes Université, 2016)
French-speaking Belgian teachers often use textbooks in their foreign language classes, especially at elementary and intermediate levels. Most modern textbooks follow the communicative approach which is based on four skills (reading, listening, speaking and writing). A few more recent textbooks adopt the action-oriented approach recommended by the Common European Framework of Reference for Languages, based on tasks that have to be fulfilled in a given set of circumstances. These textbooks have lots of qualities such as the richness of the language input and the variety of learning activities; nevertheless, they also share some features that can lead to unequal learning. This is especially true when students use the textbooks at home. In this article, three textbooks (English, German, and Spanish) are examined in the light of learning (in)equality. Results show that they share the following features: the drafting language of the textbook, the length and density of the units, the units' heterogeneous and composite nature, the inductive and "spiral" approach to grammar explanations, the lack of open-ended exercises preparing students for the complex final task, to name a few. Teachers may reduce these risks through their use of the textbooks in class provided they are aware of these characteristics and of their possible impact on unequal learning.